Two-dimensional simulation of the hydrodynamic performance of a cycloidal propeller. (1st December 2020) - Hu, Jian; Li, Tao; Guo, Chunyu
Abstract: The blade of a cycloidal propeller rotates while revolving at a constant speed, such that the angle of attack against the oncoming flow changes constantly. This characteristic working principle determines the unique hydrodynamics of cycloidal propellers. In this study, a cycloidal propeller with five blades of NACA 0012 airfoil was numerically simulated using a simplified two-dimensional model via STAR-CCM + software. The convergence of the hydrodynamical behaviors of the modeled propeller was confirmed in order to determine the gridding scheme, with special emphasis on the y + value for the blade surface, the mesh size for the computational domain, and the time step length for the simulation. The thrust, torque, and efficiency of pulsations relative to the centers of blade rotation, which were set at different positions, were computed, and the flow field and vortex distribution of were analyzed. Finally, the hydrodynamic performance of the cycloidal propeller under different operating conditions (e.g., center of blade rotation, eccentricity, advance speed, and rotary speed) were compared to determine the conditions that maximized propeller performance. The findings from this work should serve as a useful reference for improving propeller performance, as well as for optimizing future propeller designs. Highlights: The blade of a cycloidal propeller rotates while revolving at a constant speed, the angle of attack changes constantly. The advance speed and rotary speed of the cycloidal propeller greatly affect its efficiency and pulsation. The eccentricity affects the blade's rotation speed and angle of attack, which has a great impact on performance. The position of the blade rotation center greatly affects the thrust pulsation and efficiency of the cycloidal propeller.